Ternary composite adsorbent for repairing cadmium and arsenic polluted wastewater and preparation method thereof

By using the biological carbon-zero-zero-zero zero-zero-zero-zone triple composite adsorbent, the problem of removal and arsenic in waste water is solved, and high-efficiency adsorption and good circular utilization capabilities are achieved.

CN119327424APending Publication Date: 2025-01-21NORTHWEST A & F UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765964.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove cadmium and arsenic from wastewater, resulting in water pollution and endangering human health and the environment.

Method used

The nano zero-valent iron-loaded biochar-zeolite ternary composite adsorbent is prepared through the liquid phase method and liquid phase reduction method, and its ability to efficiently adsorb cadmium and arsenic is utilized.

Benefits of technology

The efficient adsorption of cadmium and arsenic in waste water, the adsorption volume reached 28.09mg/g and 186.99mg/g, respectively, and showed good regeneration and circulation capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327424A_ABST
    Figure CN119327424A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heavy metal wastewater treatment, and relates to a ternary composite adsorbent for repairing cadmium and arsenic polluted wastewater and a preparation method thereof. The ternary composite adsorbent disclosed by the invention is a nanometer zero-valent iron loaded charcoal-zeolite ternary composite adsorbent, and can effectively adsorb cadmium and arsenic in wastewater. 0.03 g of the ternary composite adsorbent is put into wastewater with the cadmium concentration of 10 mg / L and the arsenic concentration of 100 mg / L, and the adsorption effects of the composite adsorbent on cadmium and arsenic reach 28.09 mg / g and 186.99 mg / g respectively. The ternary composite adsorbent has the potential of large-scale preparation and effective application, meanwhile, the cost is reduced, and application and popularization are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy metal wastewater treatment and relates to a ternary composite adsorbent for repairing cadmium and arsenic polluted wastewater and a preparation method thereof. Background Art

[0002] Due to the rapid development of industry and agriculture, as well as the huge growth of the world's population that has disturbed the natural ecosystem, heavy metal pollution has become a serious threat to the environment and food security. Unlike organic pollutants, heavy metal pollution is hidden, persistent and irreversible, which not only reduces the quality of water, atmosphere and food crops, but also poses a huge threat to human health and well-being.

[0003] Heavy metals in environmental pollution actually mainly refer to heavy metals with significant biological toxicity, such as mercury, cadmium, lead, chromium and metalloid arsenic. At present, the most attention has been paid to mercury, cadmium and chromium. These heavy metals will remain, accumulate and migrate after entering the environment or ecosystem, causing harm. For example, heavy metals discharged with wastewater, even in low concentrations, can accumulate in algae and sediments, be adsorbed on the surface of fish and shellfish, and concentrate in the food chain, thus causing public pollution.

[0004] At present, the water environment is facing two serious problems: the rapid economic development has led to a sharp increase in the demand for water, resulting in excessive exploitation of water sources (including groundwater sources), and the shortage of water resources in many places, especially in the vast northern region, is becoming increasingly serious; at the same time, due to the constraints of economic and technical factors, the urban wastewater treatment rate is still low. A large amount of wastewater is directly discharged into natural water bodies without treatment, causing rivers and lakes to be polluted to varying degrees. It has seriously restricted economic development, endangered people's health, and caused huge losses. Wastewater containing heavy metal ions is discharged into natural water bodies without strict treatment, causing water pollution, seriously endangering human health, and causing serious harm to fishery and agricultural production. Therefore, it is crucial to transform and recycle heavy metals in water and make the discharged sewage meet the standards for life and property. Therefore, how to economically and effectively remove harmful heavy metal ions in wastewater is of great significance in water environment protection.

[0005] Nano zero-valent iron loaded biochar-zeolite is a ternary composite adsorption material that can effectively adsorb complex heavy metal pollution such as cadmium and arsenic. This material has the potential for large-scale preparation and effective application, while reducing costs and facilitating application promotion. Summary of the invention

[0006] The present invention proposes a nano zero-valent iron loaded biochar-zeolite ternary composite adsorbent based on the basic principles of a liquid phase method and a liquid phase reduction method, and provides a solution for repairing heavy metal pollution of water resources by explaining the preparation principle and preparation method of the ternary composite adsorbent.

[0007] To achieve this technical purpose, the present invention adopts the following technical solution.

[0008] In a first aspect, the present invention provides a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater, wherein the ternary composite adsorbent is composed of nano zero-valent iron, biochar and zeolite, wherein the adsorption mass ratio of biochar to zeolite is 9:1.

[0009] Preferably, the ternary composite adsorbent is prepared by loading nano zero-valent iron on a biochar-zeolite composite material.

[0010] Preferably, the loading rate of nano zero-valent iron in the ternary composite adsorbent for repairing cadmium-arsenic contaminated wastewater is 10%.

[0011] In a second aspect, the present invention provides a preparation method of a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater, the steps of which are as follows: (1) weighing 19.00 g of a biochar-zeolite composite material and pouring it into a three-necked flask, adding 67 mL of anhydrous ethanol, weighing 9.93 g of FeSO4·7H2O and dissolving it in 133 mL of deionized water, and adding the dissolved FeSO4·7H2O into the three-necked flask, wherein the ratio of deionized water to ethanol is 2:1 (v:v), shaking the solution in the three-necked flask to completely mix it, stirring it evenly to form a suspension, and then ultrasonicating it for 30 minutes; (2) controlling the speed of the suspension to 300 r / min and mechanically stirring it for 30 minutes, passing nitrogen into the three-necked flask containing the solution for 1 minute to remove the oxygen therein, and then weighing 7.12 g of KBH4 was dissolved in 100 mL of deionized water and gradually added into the three-necked flask with a syringe until no obvious bubbles were generated; (3) the mechanical stirring rate was maintained and the reaction was continued for 1 hour after the addition was completed. After the reaction was completed, the supernatant was separated by centrifugation; the mixture was washed with anhydrous ethanol for 3 times. Finally, the washed synthetic material was placed in an oven for drying and then the dried material was sealed and stored to obtain a ternary composite adsorbent.

[0012] Preferably, the preparation method of the ternary composite adsorbent includes the step of preparing a biochar-zeolite composite material, and the preparation method of the biochar-zeolite composite material is as follows: add 2g of zeolite to 500mL of deionized water, and use an ultrasonic machine to ultrasonicate for 30min to prepare a stable zeolite suspension; immerse 18g of biochar in the zeolite suspension and stir for 2h to prepare the biochar-zeolite composite material; centrifuge the raw material to separate the supernatant, and dry it in an oven at 60°C for 24h; pyrolyze the biochar-zeolite composite material at 500°C and a heating rate of 5°C / min under oxygen-limited conditions in a muffle furnace for 2h to obtain the biochar-zeolite composite material.

[0013] Preferably, the preparation method of a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater provided by the present invention is proposed based on the basic principles of a liquid phase method and a liquid phase reduction method.

[0014] Preferably, KBH4 is used in the liquid phase reduction method.

[0015] In a third aspect, there is provided application of the ternary composite adsorbent of the present invention in remediating cadmium and arsenic contaminated wastewater.

[0016] Preferably, the present invention further provides the determination conditions for the ternary composite adsorbent to adsorb cadmium and arsenic: add 0.03g of the ternary composite adsorbent to 30mL of the wastewater solution at a temperature of 25-35°C, a water pH of 3-11, a Cd concentration of 0-20ppm, and an As concentration of 0-200ppm, and the adsorption time is 15min-1440min.

[0017] Preferably, the determination conditions for the ternary composite adsorbent to adsorb cadmium and arsenic are as follows: add 0.03 g of the ternary composite adsorbent to 30 mL of the wastewater solution containing Cd and As at a temperature of 25°C, a water pH of 8, a Cd concentration of 20 ppm, and an As concentration of 100 ppm, and the adsorption time is 360 min.

[0018] Compared with the prior art, the present invention "a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater and a preparation method thereof" has the following beneficial effects:

[0019] By using the nano zero-valent iron loaded biochar-zeolite ternary composite adsorbent provided by the present invention, cadmium and arsenic in wastewater can be effectively adsorbed. When 0.03g of the ternary composite adsorbent is put into artificially polluted wastewater with a cadmium concentration of 10mg / L and an arsenic concentration of 100mg / L, the adsorption effects of the ternary composite adsorbent on cadmium and arsenic reach 28.09mg / g and 186.99mg / g, respectively, and have significant effects. And through three adsorption-analysis experiments, it is found that the adsorption effects of cadmium and arsenic can be maintained at above 6.78mg / g and 53.04mg / g. It is verified that the nano zero-valent iron loaded biochar-zeolite ternary composite adsorbent can be repeatedly recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The process and adsorption mechanism diagram for the laboratory preparation of biochar-zeolite ternary composite adsorbent loaded with nano-zero-valent iron.

[0021] Figure 2 Scanning electron microscope images of biochar-zeolite (a) and nano-zero-valent iron loaded biochar-zeolite (b).

[0022] Figure 3 Raman spectra of biochar-zeolite and nano-zero-valent iron loaded biochar-zeolite. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] This example provides the preparation principle of a ternary composite adsorbent.

[0026] The ternary composite adsorbent for repairing cadmium-arsenic composite polluted wastewater is proposed based on the basic principles of liquid phase method and liquid phase reduction method.

[0027] Figure 1 The laboratory preparation process and adsorption mechanism are presented: the main mechanisms promoting cadmium removal include precipitation / coprecipitation, complexation, surface adsorption, electrostatic adsorption and H + Replacement process. Meanwhile, the adsorption mechanisms of arsenic include oxidation, complexation, coprecipitation, surface adsorption and electrostatic adsorption.

[0028] Figure 2 The scanning electron microscopy characterization of biochar-zeolite was presented, showing that the sample surface was widely covered with a layered film, which is a common clay structure. On this basis, the surface of the nano-zero-valent iron-loaded biochar-zeolite formed a microsphere-like aggregate structure, and the nano-zero-valent iron particles were evenly dispersed on the biochar-zeolite composite matrix. With the reduction of the chains between the nano-zero-valent iron particles, the biochar-zeolite effectively eliminated the aggregation of nano-zero-valent iron, indicating that the loading of nano-zero-valent iron can enhance the adsorption effect of the composite adsorbent.

[0029] By using Raman spectroscopy, an important characterization method for carbon-based materials, we used it to analyze biochar-zeolite and nano-zero-valent iron-loaded biochar-zeolite. Figure 3 The characteristic peak corresponding to the D band appears at 1350cm -1 The G band appears at 1580cm -1 The D band reflects the carbon defects in the lattice, while the G band represents the degree of carbonization of the material. As the I(D) / I(G) ratio increases, the defects in the carbon atoms will become more and more obvious. Compared with biochar-zeolite, the higher the I(D) / I(G) value, the more lattice defects of carbon atoms in nano-zero-valent iron-loaded biochar-zeolite. Lattice defects produce more oxygen vacancies, which are conducive to the combination of metal ions with nano-zero-valent iron-loaded biochar-zeolite composite adsorbents. It shows that nano-zero-valent iron-loaded biochar-zeolite has greater potential for the adsorption of cadmium and arsenic.

[0030] Example 2

[0031] This embodiment provides a method for preparing a ternary composite adsorbent.

[0032] 2 g of zeolite was added to 500 mL of deionized water and ultrasonicated for 30 min to prepare a stable zeolite suspension. Then, 18 g of biochar was immersed in the zeolite suspension and stirred for 2 h to prepare a biochar-zeolite composite material. The biochar-zeolite composite material was centrifuged to separate the supernatant and dried in an oven at 60 ° C for 24 h; finally, the biochar-zeolite composite material was pyrolyzed at 500 ° C and a heating rate of 5 ° C / min under oxygen-limited conditions in a muffle furnace for 2 h, and the obtained biochar-zeolite composite material was further screened to a particle size of 200 mesh.

[0033] Weigh 19.00 g of biochar-zeolite composite material into a three-necked flask, add 67 mL of anhydrous ethanol, weigh FeSO4·7H2O 9.93 g was dissolved in 133 mL of deionized water, and then added to a three-necked flask after dissolution. At this time, the ratio of deionized water to ethanol was 2:1 (v:v). The solution in the three-necked flask was shaken to mix completely. After stirring to form a suspension, it was ultrasonicated for 30 minutes; (2) the suspension was mechanically stirred at a speed of 300 r / min for 30 minutes, and nitrogen was introduced into the three-necked flask containing the solution for 1 minute to remove the oxygen therein. Then 7.12 g KBH4 was weighed, dissolved in 100 mL of deionized water, and gradually added to the three-necked flask with a syringe until no obvious bubbles were generated; (3) the mechanical stirring rate was maintained, and the reaction was continued for 1 hour after the dropwise addition was completed to make the generated modified material uniform and stable. After the reaction was completed, the supernatant was separated by centrifugation; it was washed with anhydrous ethanol for 3 times. Finally, the cleaned synthetic material was placed in an oven for drying, and the dried material was sealed and stored to obtain a ternary composite adsorbent.

[0034] The chemical reaction formula is as follows:

[0035] 2Fe 2+ +BH 4- +3H2O→2Fe 0 +H2BO 3- +2H2↑+4H + (1)

[0036] 4Fe 3+ +3BH 4- +9H2O→4Fe 0 +3H2BO 3- +6H2↑+12H + (2)

[0037] Example 3

[0038] This embodiment provides the adsorption effect of the ternary composite adsorbent at a temperature of about 25°C.

[0039] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorbent adsorbs 16.54mg / kg of Cd and 164.04mg / kg of As.

[0040] Example 4

[0041] This embodiment provides the adsorption effect of the ternary composite adsorbent at a temperature of about 30°C.

[0042] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 30℃, a pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 17.39mg / kg, and the adsorption capacity for As is 168.99mg / kg.

[0043] Example 5

[0044] This embodiment provides the adsorption effect of the ternary composite adsorbent at a temperature of about 35°C.

[0045] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 35°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 22.89mg / kg, and the adsorption capacity for As is 171.95mg / kg.

[0046] Example 6

[0047] This example provides an analysis of the effect of the ternary composite adsorbent at a temperature of 25 to 35°C.

[0048] In combination with Examples 3-5, by controlling the temperature, it was found that the adsorption of Cd(II) and As(III) by the composite adsorbent gradually increased with the increase of temperature. When the temperature increased from 25°C to 35°C, the adsorption of Cd(II) and As(III) by the ternary composite adsorbent increased by 27.74% and 4.58%, respectively.

[0049] Example 7

[0050] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 3.

[0051] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 3, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 13.19mg / kg, and the adsorption capacity for As is 154.65mg / kg.

[0052] Example 8

[0053] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 4.

[0054] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 4, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 18.70mg / kg, and the adsorption capacity for As is 165.57mg / kg.

[0055] Example 9

[0056] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 5.

[0057] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a pH of about 5, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 24.10mg / kg, and the adsorption capacity for As is 169.15mg / kg.

[0058] Example 10

[0059] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH of the water body is about 6.

[0060] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 6, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 27.90mg / kg, and the adsorption capacity for As is 165.79mg / kg.

[0061] Embodiment 11

[0062] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 7.

[0063] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a pH of about 7, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 28.60mg / kg, and the adsorption capacity for As is 159.64mg / kg.

[0064] Example 12

[0065] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 8.

[0066] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 28.37mg / kg, and the adsorption capacity for As is 168.30mg / kg.

[0067] Example 13

[0068] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 9.

[0069] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 9, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 28.74mg / kg, and the adsorption capacity for As is 154.36mg / kg.

[0070] Embodiment 14

[0071] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH value of the water body is about 10.

[0072] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 10, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 25.98mg / kg, and the adsorption capacity for As is 168.58mg / kg.

[0073] Embodiment 15

[0074] This embodiment provides the adsorption effect of the ternary composite adsorbent when the pH of the water body is about 11.

[0075] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 11, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 22.49mg / kg, and the adsorption capacity for As is 164.84mg / kg.

[0076] Example 16

[0077] This example provides an analysis of the effect of the ternary composite adsorbent when the pH of the water body is 3-11.

[0078] Combined with Examples 7-15, it was found through simulating different pH values ​​of wastewater that when the initial pH value was lower than 7.0, the adsorption amount of Cd by the composite adsorbent increased with the increase of pH value. When the pH value was in the range of 6.0-9.0, the adsorption amount of Cd by the ternary composite adsorbent increased significantly, reaching a maximum adsorption amount of 28.74 mg / g at a pH of 9.0. This shows that within a wider pH range of 6.0-9.0, the ternary composite adsorbent has good adsorption performance for Cd. At a pH of 5.0, the maximum adsorption amount of As by the composite adsorbent is 169.14 mg / g. Compared with the adsorption of Cd by the composite adsorbent, it has a wider pH adaptability to As. Taking into account the influence of the initial pH value, the ternary composite adsorbent exhibits higher adsorption performance for Cd and As when the water pH is 6.

[0079] Embodiment 17

[0080] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 15 min.

[0081] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 15min. The adsorption capacity of the ternary composite adsorbent for Cd is 12.37mg / kg, and the adsorption capacity for As is 158.13mg / kg.

[0082] Embodiment 18

[0083] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 60 min.

[0084] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 60min. The adsorption capacity of the ternary composite adsorbent for Cd is 14.72mg / kg, and the adsorption capacity for As is 162.58mg / kg.

[0085] Embodiment 19

[0086] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 180 min.

[0087] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 180min. The adsorption capacity of the ternary composite adsorbent for Cd is 18.44mg / kg, and the adsorption capacity for As is 167.54mg / kg.

[0088] Embodiment 20

[0089] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 240 min.

[0090] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 240min. The adsorption capacity of the ternary composite adsorbent for Cd is 19.82mg / kg, and the adsorption capacity for As is 165.30mg / kg.

[0091] Embodiment 21

[0092] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 480 min.

[0093] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 480min. The adsorption capacity of the ternary composite adsorbent for Cd is 21.65mg / kg, and the adsorption capacity for As is 161.25mg / kg.

[0094] Embodiment 22

[0095] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 720 min.

[0096] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 720min. The adsorption capacity of the ternary composite adsorbent for Cd is 23.24mg / kg, and the adsorption capacity for As is 161.24mg / kg.

[0097] Embodiment 23

[0098] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 960 min.

[0099] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 960min. The adsorption capacity of the ternary composite adsorbent for Cd is 26.07mg / kg, and the adsorption capacity for As is 162.07mg / kg.

[0100] Embodiment 24

[0101] This example provides the adsorption effect of the ternary composite adsorbent when the adsorption time is 1440 min.

[0102] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25°C, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 1440min. The adsorption capacity of the ternary composite adsorbent for Cd is 26.03mg / kg, and the adsorption capacity for As is 162.69mg / kg.

[0103] Embodiment 25

[0104] This example provides an analysis of the effect of the ternary composite adsorbent when the adsorption time is 15 min to 1440 min.

[0105] Combined with Examples 17-24, the ternary composite adsorbent exhibited rapid adsorption of Cd(II) from 15 to 960 min. During this time period, the adsorption rate of Cd(II) by the composite adsorbent gradually increased, and the adsorption process was stable after 960 min. The adsorption equilibrium time for Cd(II) was 960 min, and the adsorption amount was 26.07 mg / g. The composite adsorbent adsorbed As(III) very quickly in a very short period of time, 0-15 min, until the adsorption reached a maximum value of 167.54 mg / g at 180 min. In the 180-480 min stage, the adsorption amount of As(III) changed only slightly, and the adsorption capacity of the ternary composite adsorbent was relatively stable during this period. In summary, the adsorption effect of the ternary composite adsorbent on Cd(II) and As(III) was analyzed, and the optimal adsorption time was 360 min.

[0106] Embodiment 26

[0107] This example provides the adsorption effect of the ternary composite adsorbent after optimizing the adsorption conditions.

[0108] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 35°C, a water pH of about 6, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial concentrations of cadmium and arsenic are moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 360min. The adsorption capacity of the adsorbent for Cd is 28.09mg / kg, and the adsorption capacity for As is 186.99mg / kg.

[0109] By optimizing the adsorption conditions, the adsorption of Cd(II) and As(III) by the ternary composite adsorbent reached the maximum value.

[0110] Embodiment 27

[0111] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 0 ppm and the As concentration is 100 ppm.

[0112] There is a simulated wastewater containing As(III) with a temperature of about 25°C, a pH of about 8, and an As concentration of 100 ppm. Analysis shows that the initial arsenic concentration is moderate. 0.03 g of composite adsorbent is added to 30 mL of the wastewater solution, the adsorption time is 24 h, and the adsorption capacity of the adsorbent for As is 155.57 mg / kg.

[0113] Embodiment 28

[0114] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 2 ppm and the As concentration is 100 ppm.

[0115] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 2ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is low and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 4.96mg / kg, and the adsorption capacity for As is 159.00mg / kg.

[0116] Embodiment 29

[0117] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 4 ppm and the As concentration is 100 ppm.

[0118] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 4ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is low and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 9.25mg / kg, and the adsorption capacity for As is 156.59mg / kg.

[0119] Embodiment 30

[0120] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 6 ppm and the As concentration is 100 ppm.

[0121] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 6ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is low and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 12.61mg / kg, and the adsorption capacity for As is 154.25mg / kg.

[0122] Embodiment 31

[0123] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 8 ppm and the As concentration is 100 ppm.

[0124] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 8ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is low and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 14.22mg / kg, and the adsorption capacity for As is 148.01mg / kg.

[0125] Embodiment 32

[0126] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 100 ppm.

[0127] There is a simulated wastewater body containing Cd(II) and As(III), the temperature is about 25℃, the water pH is about 8, the Cd concentration is 10ppm, and the As concentration is 100ppm. Analysis shows that the initial cadmium concentration is moderate, the initial arsenic concentration is moderate, 0.03g of composite adsorbent is added to 30mL of wastewater solution, the adsorption time is 24h, and the adsorption capacity of Cd and As by the ternary composite adsorbent is 16.51mg / kg, and the adsorption capacity of As is 155.25mg / kg.

[0128] Embodiment 33

[0129] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 15 ppm and the As concentration is 100 ppm.

[0130] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 15ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is high and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 18.70mg / kg, and the adsorption capacity for As is 148.61mg / kg.

[0131] Embodiment 34

[0132] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 20 ppm and the As concentration is 100 ppm.

[0133] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 20ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is high and the initial arsenic concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 22.70mg / kg, and the adsorption capacity for As is 153.47mg / kg.

[0134] Embodiment 35

[0135] This example provides an analysis of the effect of the ternary composite adsorbent when the Cd concentration is 0-20 ppm and the As concentration is 100 ppm.

[0136] In combination with Examples 27-34, at the same As(III) concentration, the adsorption amount of Cd(II) by the adsorbent increases with the increase of Cd concentration in the solution, and the adsorption amount of Cd(II) gradually increases from 0 to 22.69 mg / g. The adsorption amount of As(III) by the ternary composite adsorbent is almost unaffected and is between 148.01-159.00 mg / g.

[0137] Embodiment 36

[0138] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 0 ppm.

[0139] There is a simulated wastewater containing Cd(II) with a temperature of about 25°C, a pH of about 8, and a Cd concentration of 10ppm. Analysis shows that the initial Cd concentration is moderate. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of Cd by the ternary composite adsorbent is 29.18mg / kg.

[0140] Embodiment 37

[0141] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 20 ppm.

[0142] There is a simulated wastewater body containing Cd(II) and As(III), the temperature is about 25℃, the pH of the water is about 8, the Cd concentration is 10ppm, and the As concentration is 20ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is low. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of Cd and As by the ternary composite adsorbent is 27.07mg / kg, and 10.78mg / kg respectively.

[0143] Embodiment 38

[0144] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 40 ppm.

[0145] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 40ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is low. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 25.16mg / kg, and the adsorption capacity for As is 46.37mg / kg.

[0146] Embodiment 39

[0147] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 60 ppm.

[0148] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 60ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is low. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 23.55mg / kg, and the adsorption capacity for As is 80.79mg / kg.

[0149] Embodiment 40

[0150] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 80 ppm.

[0151] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 80ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is low. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 22.36mg / kg, and the adsorption capacity for As is 119.18mg / kg.

[0152] Embodiment 41

[0153] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 100 ppm.

[0154] There is a simulated wastewater body containing Cd(II) and As(III), the temperature is about 25℃, the water pH is about 8, the Cd concentration is 10ppm, and the As concentration is 100ppm. Analysis shows that the initial cadmium concentration is moderate, the initial arsenic concentration is moderate, 0.03g of composite adsorbent is added to 30mL of wastewater solution, the adsorption time is 24h, and the adsorption capacity of Cd and As by the ternary composite adsorbent is 20.16mg / kg, and the adsorption capacity of As is 154.00mg / kg.

[0155] Embodiment 42

[0156] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 150 ppm.

[0157] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 150ppm, and an As concentration of 40ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is high. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 17.57mg / kg, and the adsorption capacity for As is 186.44mg / kg.

[0158] Embodiment 43

[0159] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 200 ppm.

[0160] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a water pH of about 8, a Cd concentration of 10ppm, and an As concentration of 200ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is high. 0.03g of composite adsorbent is added to 30mL of wastewater solution, and the adsorption time is 24h. The adsorption capacity of the ternary composite adsorbent for Cd is 16.13mg / kg, and the adsorption capacity for As is 222.04mg / kg.

[0161] Embodiment 44

[0162] This embodiment provides the adsorption effect of the ternary composite adsorbent when the Cd concentration is 10 ppm and the As concentration is 0-200 ppm.

[0163] Combined with Examples 36-43, at the same Cd(II) concentration, the adsorption of As(III) by the ternary composite adsorbent increased with the increase of As(III) concentration, with a peak value of 222.04 mg / g. However, due to the limited adsorption sites, the adsorption of Cd(II) decreased from 29.18 mg / g to 16.13 mg / g.

[0164] Embodiment 45

[0165] This embodiment provides the adsorption effect of the ternary composite adsorbent reused for the first time when the Cd concentration is 10 ppm and the As concentration is 100 ppm.

[0166] There is a simulated wastewater containing Cd(II) and As(III), the temperature is about 25℃, the pH of the water is about 8, the Cd concentration is 10ppm, and the As concentration is 100ppm. Analysis shows that the initial concentration of cadmium is moderate, the initial concentration of arsenic is moderate, 0.3g of composite adsorbent is added to 30mL of wastewater solution, the adsorption time is 24h, and the adsorption amount of Cd by the adsorbent is 8.67mg / kg, and the adsorption amount of As is 56.83mg / kg. This is the adsorption effect of the ternary composite adsorbent when it is used for the first time.

[0167] After adsorption equilibrium (24 hours), the residue was washed three times with anhydrous ethanol and then dried for 24 hours. After drying, the residue saturated with adsorbed ions was placed in 30mL 0.1mol / L NaOH for the first desorption experiment. After 24 hours, it was centrifuged and washed three times with anhydrous ethanol to obtain the ternary composite adsorbent for the second reuse.

[0168] Embodiment 46

[0169] This embodiment provides the adsorption effect of the ternary composite adsorbent reused for the second time when the Cd concentration is 10 ppm and the As concentration is 100 ppm.

[0170] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is moderate. 30mL of the wastewater solution is added to the ternary composite adsorbent reused for the second time, and the adsorption time is 24h. The adsorption capacity of the adsorbent for Cd is 7.76mg / kg, and the adsorption capacity for As is 55.64mg / kg.

[0171] After adsorption equilibrium (24 hours), the residue was washed three times with anhydrous ethanol and then dried for 24 hours. After drying, the residue saturated with adsorbed ions was placed in 30mL 0.1mol / L NaOH for the second desorption experiment. After 24 hours, it was centrifuged and washed three times with anhydrous ethanol to obtain the ternary composite adsorbent for the third reuse.

[0172] Embodiment 47

[0173] This embodiment provides the adsorption effect of the ternary composite adsorbent reused for the third time when the Cd concentration is 10 ppm and the As concentration is 100 ppm.

[0174] There is a simulated wastewater body containing Cd(II) and As(III), with a temperature of about 25℃, a pH of about 8, a Cd concentration of 10ppm, and an As concentration of 100ppm. Analysis shows that the initial cadmium concentration is moderate and the initial arsenic concentration is moderate. 30mL of the wastewater solution is added to the second reused ternary composite adsorbent, and the adsorption time is 24h. The adsorbent adsorbs 6.78mg / kg of Cd and 53.04mg / kg of As.

[0175] From Examples 45-47, it is described that the ternary composite adsorbent was subjected to three adsorption-desorption cycles. After three cycles, the adsorption capacity of the ternary composite adsorbent decreased, but the adsorption capacity still reached 6.78 mg / kg and 53.04 mg / kg, respectively. In general, the ternary composite adsorbent has good regeneration and recycling capabilities.

[0176] The embodiments described above are only some embodiments of the present invention, not all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.

Claims

1. A ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater, characterized in that: The ternary composite adsorbent is composed of nano zero-valent iron, biochar and zeolite, wherein the adsorption mass ratio of the biochar to the zeolite is 9:

1.

2. The ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to claim 1, characterized in that: The ternary composite adsorbent is prepared by loading nano zero-valent iron on a biochar-zeolite composite material.

3. The ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to claim 2, characterized in that: The loading rate of the nano zero-valent iron is 10%.

4. The method for preparing the ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to any one of claims 1 to 3, characterized in that: include: (1) Weigh 19.00 g of biochar-zeolite composite material and pour it into a three-necked flask, add 67 mL of anhydrous ethanol, weigh 9.93 g of FeSO4·7H2O and dissolve it in 133 mL of deionized water. After dissolution, add it to the three-necked flask. At this time, the ratio of deionized water to ethanol is 2:1 (v:v). Shake the solution in the three-necked flask to mix it completely, stir it evenly to make a suspension, and then ultrasonicate it for 30 minutes; (2) Control the speed of 300 r / min to mechanically stir the suspension for 30 minutes, pass nitrogen into the three-necked flask containing the solution for 1 minute to remove the oxygen therein, and then weigh 7.12 g KBH4 was dissolved in 100 mL of deionized water and gradually added into the three-necked flask with a syringe until no obvious bubbles were generated; (3) the mechanical stirring rate was maintained and the reaction was continued for 1 hour after the addition was completed. After the reaction was completed, the supernatant was separated by centrifugation; the mixture was washed with anhydrous ethanol for 3 times. Finally, the washed synthetic material was placed in an oven for drying and then the dried material was sealed and stored to obtain a ternary composite adsorbent.

5. The method for preparing a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to claim 4, characterized in that: The invention comprises the steps of preparing a biochar-zeolite composite material, wherein the preparation method of the biochar-zeolite composite material is as follows: adding 2g of zeolite into 500mL of deionized water, ultrasonicating with an ultrasonic machine for 30min to prepare a stable zeolite suspension; immersing 18g of biochar into the zeolite suspension and stirring for 2h to prepare the biochar-zeolite composite material; centrifuging the biochar-zeolite composite material through a centrifuge to separate the supernatant, and drying in an oven at 60°C for 24h; pyrolyzing the biochar-zeolite composite material at 500°C and a heating rate of 5°C / min under oxygen-limited conditions in a muffle furnace for 2h to obtain the biochar-zeolite composite material.

6. The method for preparing a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to claim 4, characterized in that: The preparation method is proposed based on the basic principles of a liquid phase method and a liquid phase reduction method.

7. The method for preparing a ternary composite adsorbent for repairing cadmium and arsenic contaminated wastewater according to claim 6, characterized in that: The liquid phase reduction method uses KBH4.

8. Use of the ternary composite adsorbent according to claim 1 in remediating cadmium and arsenic contaminated wastewater.

9. The use according to claim 8, characterized in that The determination conditions for the ternary composite adsorbent to adsorb cadmium and arsenic are as follows: adding 0.03 g of the ternary composite adsorbent to 30 mL of the wastewater solution containing simulated wastewater containing Cd and As at a temperature of 25 to 35° C., a water pH of 3 to 11, a Cd concentration of 0 to 20 ppm, and an As concentration of 0 to 200 ppm, and the adsorption time is 15 min to 1440 min.

10. The use according to claim 8, characterized in that The determination conditions for the ternary composite adsorbent to adsorb cadmium and arsenic are as follows: 0.03 g of the ternary composite adsorbent is added to 30 mL of the wastewater solution containing Cd and As at a temperature of 25° C., a water pH of 8, a Cd concentration of 20 ppm, and an As concentration of 100 ppm, and the adsorption time is 360 min.